Low-Dose Decitabine Inhibits Cytotoxic T Lymphocytes-Mediated Platelet Destruction via Modulating PD-1 Methylation in Immune Thrombocytopenia - Han, Panpan; Yu, Tianshu; Hou, Yu; Zhao, Yajing; Liu, Yang; Sun, Yunqi; Wang, Haoyi; Xu, Pengcheng; Li, Guosheng; Sun, Tao; Hu, Xiang; Liu, Xinguang; et al. (Frontiers in Immunology, 2021)
Cytotoxic T lymphocytes (CTLs)-mediated platelet destruction plays an important role in the pathogenesis of primary immune thrombocytopenia (ITP). The programmed cell death protein 1 (PD-1) signaling can turn off autoreactive T cells and induce peripheral tolerance. Herein, we found that the expression of PD-1 and its ligand PD-L1 on CD8+ T cells from ITP patients was decreased. Activating PD-1 pathway by PD-L1-Fc fusion protein inhibited CTLs-mediated platelet destruction in ITP in vitro. PD-1 promoter hypermethylation in CD8+ T cells was found in ITP patients, resulting in decreased PD-1 expression. The demethylating agent decitabine at a low dose was proved to restore the methylation level and expression of PD-1 on CD8+ T cells and reduce the cytotoxicity of CTLs of ITP patients. The phosphorylation levels of phosphatidylinositol 3-kinase (PI3K) and AKT in CD8+ T cells were significantly downregulated by low-dose decitabine. Furthermore, blocking PD-1 could counteract the effect of low-dose decitabine on CTLs from ITP patients. Therefore, our data suggest that the aberrant PD-1/PD-L1 pathway is involved in the pathophysiology of ITP and enhancing PD-1/PD-L1 signaling is a promising therapeutic approach for ITP management. Our results reveal the immunomodulatory mechanism of low-dose decitabine in ITP by inhibiting CTLs cytotoxicity to autologous platelets through PD-1 pathway.